Mengaplikasikan SERVQUAL pada Konser Musik: Dimensi Tangibles dan Dimensi Reliabilitas Menjelaskan 92 % Kepuasan Konsumen - Wakari, Tesalonika Sifren; Simamora, Bilson (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Institut Bisnis dan Informatika Kwik Kian Gie, 2024)
TThe success of a concert is determined not only by the presence of musicians but also how the concert promoter is managed. Service quality plays a crucial role in shaping consumer satisfaction. Chosing Dyandra Global Edutainment, this study utilize two dimensions of SERVQUAL perceived as the most suitable for a concert: Tangibility and Reliability. The study aims to investigate their role in creating consumers satisfaction. Therefore, the authors collect the data with questionnaire distributed via Google Forms shared on the social media platform X to 100 respondents. Data analysis with Structural Equation Modeling (SEM) supported by SmartPLS 4 reveals that the tangibles and reliability dimensions positively influence customer satisfaction with the determination of 92%. The result suggest that event organizers should prioritize tangible and reliability dimensions. This study has not investigated the influence of the quality of celebrity image on consumer satisfaction. Future studies can investigate that issue.